Scientific support of competition development processes in power market - V. Ya. Afanasyev; V. V. Kuzmin; I. N. Ivanov (Управление, 2024)
The article studies the issues of competition development processes scientific support in the Russian power market. Based on the study results and the Russian electric power market current model experience evaluation, conclusions have been drawn about the need for additional research into the competition development in the market with the subsequent development and a new set of scientifically sound measures implementation to create acceptable conditions for competition of its subjects. The market properties in many respects diverge from the properties of markets with developed competition. The market has not yet managed to create any acceptable competition conditions, forming systemic conditions for a noticeable increase in the entrepreneurship efficiency. It is characterized by the presence of serious systemic problems that have a significant negative impact on its subjects functioning efficiency and require solutions. The article analyzes the directions and areas of insufficient scientific study on the issues of market interaction between consumers and electric power producers as important reasons for the the modern Russian power market problems persistence. The paper characterizes the complex of research and design developments for a new package of interrelated science-based measures implementation for competition conditions development in the power market, aimed at bringing its properties closer to the properties of markets with developed competition.